Early uterine rupture mimicking pancreatitis in the early second trimester of pregnancy: a case report - Bhatti, Saira; Ashfaq, Sana; Parveen, Shakira (Journal of the Pakistan Medical Association, 2026)
The case of a 28-year-old woman with prior caesarean deliveries, who came in with severe abdominal pain along with 18 weeks of gestation, is presented. Ultrasound showed a live intrauterine pregnancy accompanied with oedematous pancreas and mild to moderate fluid in the abdomen. Despite supportive care, her condition deteriorated with dropping haemoglobin and worsening abdominal pain. Computed tomography (CT) scan suggested possible appendicitis or focal uterine rupture. Despite conservative management her pain persisted. Repeat ultrasound revealed a uterine wall defect with placenta protruding through it, suggestive of uterine rupture. Emergency laparotomy confirmed uterine rupture at the previous uterine scar, with placenta percreta invading the bladder wall. During the procedure, the patient had an estimated blood loss of 2,000ml. After receiving antibiotics and blood transfusions, she recovered and was discharged after 21 days. This case highlights a rare but life-threatening complication of a second-trimester uterine rupture in a scarred uterus. Keywords: Placenta accreta syndrome, Spontaneous uterine rupture, Second-trimester, Placenta percreta.